Motivation Study with Prevention of Diabetic Foot Injuries in Gorontalo Province - Pakaya, Nasrun; Y Dulahu, Wirdha; Aswad, Ahmad (Journal of Health Education, 2024)
Background: The World Health Organization (WHO) survey results show that the number of people with diabetes mellitus in Indonesia is ranked the 4th largest globally. Diabetic ulcers are one of the complications that are often found in people with diabetes. Patients with Type II DM need high motivation in carrying out their therapy because the therapy undergone causes boredom, especially when there has been a complication in the form of diabetic ulcers. The purpose of this study is to determine the relationship between intrinsic and extrinsic motivation and actions to prevent diabetic foot injuries, which includes the use of drugs, diet, physical activity, and monitoring of diabetic patients in Gorontalo Province.Methods: This study used a cross-sectional design with a sample of 287 respondents. Data collection instrument in the form of a questionnaire with bivariate analysis using the Chi-Square statistical testResults: The Chi-Square statistical test showed a relationship between motivation and diabetic foot injury prevention measures, both intrinsic motivation and extrinsic motivation, with p-value = 0.000 (α = 0.05).Conclusion: There was a relationship between intrinsic and extrinsic motivation and the prevention of foot wounds in people with diabetes in Gorontalo Province. This research is expected to increase motivation so that diabetic foot injuries can be prevented optimally.